Knowledge, Attitude and Practice Regarding Hepatitis B among Preclinical Medical Students and Their Vaccination Status at a Private Medical College in Sylhet (Jalalabad Medical Journal, 2025)
Hepatitis B is a worldwide disease that affects millions of people. Vaccination and preventive knowledge are crucial for all, especially health care professionals. This study was aimed at evaluating the hepatitis B vaccination status of preclinical medical students and their knowledge, awareness and practice regarding hepatitis B infection. This was a descriptive type of cross-sectional study that was conducted in Jalalabad Ragib-Rabeya Medical College, Sylhet, from January 1, 2022, to June 30, 2022. The data was collected using a semi-structured questionnaire. The statistical analysis was done using SPSS version 20. Among the total of 192 preclinical students in the study, 51% were female and the rest were male. The percentages of students belonging to the 1st and 2nd academic years of MBBS were almost equal (49% and 51%, respectively). Less than half of the participants (48.4%) were vaccinated, whereas only 23.9% were fully vaccinated against the hepatitis B vaccine. The study found that lack of knowledge was the main reason for not getting vaccinated among the non-vaccinated students (51%). Only 31.2% of preclinical students had good knowledge, attitude, and practice regarding hepatitis B. Those who had more knowledge regarding hepatitis B were practicing more preventive measures (Spearman’s correlation coefficient=0.209, p